Digital Ecosystem Standardization of the Quranic Literacy: A Policy Strategy to Mitigate the Impact of Fear of Missing Out and Public Attention Disruption - Abdul Syukur (AMUYA: JOURNAL OF MANAGEMENT, 2026)
The low intensity and quality of public engagement with Quranic literacy requires attention due to the dominance of digital disruption, which erodes attention spans through the culture of infinite scrolling and digital dopamine addiction. The urgency of this issue lies in the phenomenon of Fear of Missing Out (FoMO) and content fragmentation that impairs cognitive capacity for deep reading, resulting in engagement with the Qur’an being outcompeted by time spent on digital devices. This policy paper adopts a descriptive qualitative methodology, utilizing the Urgency, Seriousness, and Growth (USG) method for problem prioritization and William N. Dunn’s framework to evaluate policy alternatives based on effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The analysis indicates that digital disruption is the most urgent issue with the highest score (14), necessitating structural intervention through the standardization of the digital ecosystem to mitigate extraneous cognitive load and restore public focus. The discussion recommends the issuance of a Decree of the Minister of Religious Affairs (KMA) regarding the Standardization and Acceleration of the National Quranic Literacy Digital Ecosystem as a primary strategy to regulate key actors, such as the Lajnah Pentashihan Mushaf Al-Qur'an (LPMQ) and application developers, to ensure content authenticity and maintain the quality of user attention amidst the surge of instant information.